UPAYA MENINGKATKAN KEMAMPUAN PERCAKAPAN MELALUI METODE MATERNAL REFLEKTIF ANAK TUNARUNGU - Fitriawati - Fitriawati (Jurnal Penelitian Pendidikan Khusus, 2013)
This research is back-grounded by a problem on deaf children whose could read but did not know the meaning, this caused by the teacher has not been optimal yet in applying Maternal Reflective Method to increase the ability in speaking in simple reading text. This research aimed to describe the applied of Maternal Reflective Method in increasing the reading ability in Indonesian Language Instruction. Execution start on reading with the right rhythm according with bend of phrase/sentence fragment in conversation with face directed and voice directed. The research used an action research class design collaborated with colleagues. The subject of research is the third class of SLBN Tanjung Pinang with five deaf students. Among this students there was two students have not yet understood contents of reading simple text, so as to could not answered the question according to contents of reading simple texts. The result of the research on first cyclic with applying Maternal Reflective Method has not got succeed yet, and then continued at second cyclic with applying Maternal Reflective Method that having got the result in increasing conversation. Based on result of the research, could conclude that applying the Maternal Reflective Method could increase ability in conversation for deaf students. From the result, thus to increase the ability the conversation on the deaf student could be applied the Maternal Reflective Method. Suggested that the teacher of the deaf student at the best in teaching subject of Bahasa Indonesia especially according with conversation using Maternal Reflective Method.